PENGEMBANGAN LKPD BERBASIS STEM PADA MATERI HIMPUNAN KELAS VII SMP/MTs - Maichia Meimolly Viodelf (Departemen Matematika, 2022)
Based on the results of preliminary research, it is known that in the learning process students are fixated on the use of LKS purchased from publishers, this has not optimized students to be able to think critically, be able to connect science with the real world, mastery of technology and information, which is a 21st century learning paradigm. based on advances in technology and science. Therefore, a teaching material in the form of a STEM-based LKPD was designed on the set material. This research includes development research using the Plomp model which consists of three stages, namely the preliminary research stage, the development or prototyping phase, and the assessment phase. This research produces STEM-based worksheets on set material that is valid and practical for the learning process Keywords — Research Development, LKPD, Sets, STEM, Plomp Development Model